The development of human resources in the University of Dili, Timor-Leste (A rector’s policy study) - Cabral, Horacio da Costa Guterres; Djaha, Ajis SA; Nursalam, Nursalam (goodwood publishing, 2019)
Abstract Purpose: This research aims to obtain a description of the policy of developing human resource educators at the University of Dili in accordance with applicable academic regulations. Research methodology: The method used in this research was a descriptive qualitative method. Six respondents were determined as research samples. The research instruments for this study were interview guides, notebooks, recording devices, test books and researchers. Data collection was done through interview method and the data was analyzed by referring to Miles and Huberman's Intractive model framework. Results: there are some efforts to develop the human resources of educators in universities such as sending of teaching staff to continue their education and various policies that enable the development of educators' human resources. Some factors that influence the development of human resource educators in universities are the organizational structure, organizational policies, allocation of funds, the level of educators’ education and the participation of educators in support for the development of human resources Limitations: this research only discusses the development of educators as human resources at the University of Dili and various factors that influence it. Contribution: This research was conducted to answer problems related to the management of development for educators as human resources at the University of Dili and what factors influence the development of teaching human resources at the University of Dili Timor-Leste Keywords: Development, Human resource, Educator